MicroRNA-140-5p represses chondrocyte pyroptosis and relieves cartilage injury in osteoarthritis by inhibiting cathepsin B/Nod-like receptor protein 3 - Lei Zhang (Taylor & Francis Group, 2021)
Osteoarthritis (OA) is a degenerative joint disease. Dysregulated microRNA (miRNA) expressions are implicated in OA progression. Consequently, the current study set out to investigate the mechanism of miR-140-5p in OA cartilage injury. Firstly, the murine and cell models of OA were established, and cartilage tissues of OA mice were observed using hematoxylin and eosin staining and safranin O staining. Chondrocyte pyroptosis was further assessed using immunohistochemical and Calcein-AM/PI staining. The levels of gasdermin-D (GSDMD)-N, cleaved caspase-1, interleukin (IL)-1β, and IL-18 in cartilage tissues and cells were determined using Western blot and enzyme-linked immunosorbent assay kits. The targeting relationship between miR-140-5p and cathepsin B (CTSB) was verified using a dual-luciferase assay. Moreover, the binding of CTSB and Nod-like receptor protein 3 (NLRP3) was detected using co-immunoprecipitation assay. Lastly, the effects of NLRP3 activation and CTSB overexpression on chondrocyte pyroptosis were documented. It was found that OA induction aggravated cartilage tissue injury and enhanced chondrocyte pyroptosis. miR-140-5p was poorly-expressed in OA models, and miR-140-5p over-expression alleviated chondrocyte pyroptosis, as evidenced by decreased GSDMD-N, cleaved caspase-1, IL-1β, and IL-18 levels. miR-140-5p targeted the CTSB gene, whereas CTSB further bound to NLRP3 and activated the NLRP3 inflammasome. Additionally, CTSB over-expression or NLRP3 activation reversed the inhibitory effect of miR-140-5p on chondrocyte pyroptosis. Collectively, our findings revealed that miR-140-5p repressed chondrocyte pyroptosis and alleviated OA cartilage injury via inhibition of the CTSB/NLRP3. This study may confer a theoretical basis for the treatment of OA cartilage injury.